Structure, mechanism, and performance evaluation of natural gas hydrate kinetic inhibitors - Shahnazar, Sheida; Bagheri, Samira; TermehYousefi, Amin; Mehrmashhadi, Javad; Sayuti, Mohd; Kadri, Nahrizul Adib (De Gruyter, 2018)
Ice-like crystal compounds, which are formed in low-temperature and high-pressure thermodynamic conditions and composed of a combination of water molecules and guest gas molecules, are called gas hydrates. Since its discovery and recognition as the responsible component for blockage of oil and gas transformation line, hydrate has been under extensive review by scientists. In particular, the inhibition techniques of hydrate crystals have been updated in order to reach the more economically and practically feasible methods. So far, kinetic hydrate inhibition has been considered as one of the most effective techniques over the past decade. This review is intended to classify the recent studies regarding kinetic hydrate inhibitors, their structure, mechanism, and techniques for their performance evaluation. In addition, this communication further analyzes the areas that are more in demand to be considered in future research.